Changes in the Structural-Phase State and Dislocation Density of Ti49.8Ni50.2 Alloy Depending on the Isochronal Annealing Temperature after Severe Plastic Deformation by abc Pressing at 573 K; Physical Mesomechanics; Vol. 27, iss. 2 - Mironov Yu. P. Yury Petrovich; Lotkov A. I. Aleksandr Ivanovich; Grishkov V. N. Valery Nikolaevich; Laptev R. S. Roman Sergeevich; Gusarenko A. A. Aleksandr Aleksandrovich; Barmina E. G. Elena Georgievna (2024, 2024)
Title screen